Fatal choking in infants and children treated in a pediatric intensive care unit: A 7- year experience. (July 2018) - Wu, Xiling; Wu, Lei; Chen, Zhimin; Zhou, Yunlian
Abstract: Introduction: Foreign bodies aspiration can lead to significant morbidity, few have examined in detail the deaths resulting from foreign bodies aspiration. Methods: We conducted a review of children who presented to the pediatric intensive care unit of a university hospital due to fatal foreign bodies aspiration during the period of 2010–2017. Result: Of the 28 patients, 17 (61%) patients were male and 11 (39%) were female. The range of age was 1–63 months, with mean of 15.2 months. The common foreign bodies included milk, nuts and fruits. Majority of them had round shapes. All the patients died due to asphyxia or serious complications after foreign bodies aspiration. Conclusions: Prevention and early recognition remains a critical factor to reduce the mortality of foreign bodies aspiration.